Detection of Colistin Resistance in Salmonella enterica Using MALDIxin Test on the Routine MALDI Biotyper Sirius Mass Spectrometer - Dortet, Laurent; Bonnin, Rémy A.; Le Hello, Simon; Fabre, Laetitia; Bonnet, Richard; Kostrzewa, Markus; Filloux, Alain; Larrouy-Maumus, Gerald (Frontiers in Microbiology, 2020)
Resistance to polymyxins in most Gram-negative bacteria arises from chemical modifications to the lipid A portion of their lipopolysaccharide (LPS) mediated by chromosomally-encoded mutations or the recently discovered plasmid-encoded mcr genes that have further complicated the landscape of colistin resistance. Currently, MIC determination by broth microdilution, the gold standard for the detection of polymyxin resistance, is time consuming (24 hours) and challenging to perform in clinical and veterinatry laboratories. Here we present the use of the MALDIxin to detect colistin resistant Salmonella enterica using the MALDxin test on the routine MALDI Biotyper Sirius system.